1998
DOI: 10.1016/s0014-5793(98)01255-1
|View full text |Cite
|
Sign up to set email alerts
|

The SH2 domain containing inositol 5‐phosphatase SHIP2 displays phosphatidylinositol 3,4,5‐trisphosphate and inositol 1,3,4,5‐tetrakisphosphate 5‐phosphatase activity

Abstract: Distinct forms of inositol and phosphatidylinositol polyphosphate 5-phosphatases selectively remove the phosphate from the 5-position of the inositol ring from both soluble and lipid substrates. SHIP1 is the 145-kDa SH2 domain-containing inositol 5-phosphatase expressed in haematopoietic cells. SHIP2 is a related but distinct gene product. We report here that SHIP2 can be expressed in an active form both in Escherichia coli and in COS-7 cells. A truncated 103-kDa recombinant protein could be purified from bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 14 publications
3
103
0
Order By: Relevance
“…This protein, referred to as SHIP-2, displays enzymic activity comparable to that of SHIP-1. The substrates in itro are Ins(1,3,4,5)P % and PtdIns(3,4,5)P $ [20,21]. Recent work by Habib et al [21] has demonstrated that 51C\SHIP-2 associates with Shc in human non-haemopoietic cell lines stimulated with growth factors and insulin.…”
Section: Figure 1 Alignment Of Ship-1 and Ship-2 Sequencesmentioning
confidence: 99%
“…This protein, referred to as SHIP-2, displays enzymic activity comparable to that of SHIP-1. The substrates in itro are Ins(1,3,4,5)P % and PtdIns(3,4,5)P $ [20,21]. Recent work by Habib et al [21] has demonstrated that 51C\SHIP-2 associates with Shc in human non-haemopoietic cell lines stimulated with growth factors and insulin.…”
Section: Figure 1 Alignment Of Ship-1 and Ship-2 Sequencesmentioning
confidence: 99%
“…SHIPs are tyrosine-phosphorylated proteins with several interesting features: an amino-terminal SH2 domain, a central catalytic domain and, at the carboxyl tail, several NPxY motifs [able to interact with phosphotyrosine-binding domain (PTB)] and Src homology 3-interacting prolinerich motifs (Drayer et al, 1996;Pesesse et al, 1997;Erneux et al, 1998;Majerus et al, 1999;Rohrschneider et al, 2000). Because of their ability to interact with SH2/PTB-containing protein, such as Src homology 2 domain-containing transforming protein 1 (Shc) (Pradhan and Coggeshall, 1997), and to dephosphorylate phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P 3 ] (Drayer et al, 1996;Pesesse et al, 1998), the SHIPs have the potential to regulate the Ras/MAP kinase pathway and many, if not all, PI 3K induced events.…”
mentioning
confidence: 99%
“…PI3K phosphorylates PI(4,5)P 2 to create PI(3,4,5,)P 3 [33] and SHIP2 is a negative regulator of the PI3K pathway [17] that dephosphorylates PI(3,4,5)P 3 lipids to PI(3,4)P 2 [15]. Importantly, as shown previously by us, Arap3 binds PI(3,4,5,)P 3 stronger than it binds PI(3,4)P 2 [3].…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit polyclonal anti-SHIP2 antibody and sheep anti-Arap3 antibody were described before [3,15]. Where indicated, cells were stimulated with 20 ng/ml EGF (ICN Biomedicals Inc.), 1 μg/ml insulin (Sigma) and 10 μM LY294002 (Sigma).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation